Early solar irradiation as a source of the inner solar system chromium isotopic heterogeneity. (5th November 2021) - Kadlag, Yogita; Hirtz, Jason; Becker, Harry; Leya, Ingo; Mezger, Klaus
Abstract: Different solar system objects display variable abundances of neutron‐rich isotopes such as 54 Cr, 50 Ti, and 48 Ca, which are commonly attributed to a heterogeneous distribution of presolar grains in different domains of the solar system. Here, we show that the heterogeneity of 54 Cr/ 52 Cr and the correlation of 54 Cr/ 52 Cr with Fe/Cr in metal fractions of EH3 chondrites and in inner solar system bodies can be attributed to variable irradiation of dust grains by solar energetic particles and variable mixing of irradiated material in the different domains of the inner solar nebula. The isotope variations in inner solar system objects can be generated by ~300 y long local irradiation of mm‐ to cm‐sized solids with average solar energetic particle fluxes of ~10 5 times the modern value. The relative homogeneity of 53 Cr/ 52 Cr in inner solar system objects can be a consequence of the production of 53 Mn by the early irradiation of dust, evaporation, and nebula‐wide homogenization of Mn due to high temperatures, followed by Mn/Cr fractionation within the first few million years of the solar system. The 54 Cr/ 52 Cr of the Earth can be produced by irradiated pebbles and <15 wt% of CI chondrite like material. Alternatively, Earth may contain only a few % of CI chondrite like material but then must have an Fe/Cr ratio 10–15% higher than CI chondrites.